Analysis of Urban Residents’ Consumption Behavior and Influencing Factors of Ecological Agricultural Products in the Post-Pandemic Era of COVID-19 - Ximing Chen; Jie Shang (Applied Bionics and Biomechanics)
Based on consumer survey data in the post-pandemic era of COVID-19, a binary Logit model was used to analyze the consumers’ consumption behavior and the influencing factors of ecological agricultural products in the post-pandemic era. The results showed that: family size, average annual household income, gender, and education level would not affect the consumers’ behavior in purchasing ecological agricultural products after the pandemic; age and whether consumers have purchased agricultural products before had a significant negative impact on consumption behavior; the degree of consumers’ skepticism about agricultural products in the market after the pandemic had a significant positive impact on their purchase behavior. According to the analysis results, it is proposed that: we should vigorously develop the connection between agricultural socialized service industry and large supermarkets, improve the online and offline sales model of ecological agricultural products, establish an ecological agricultural product service platform, and enhance the scientific and technological researches and their application to ecological agricultural products.